UNVEILING RESEARCH PATTERNS IN PERSONALITY TRAITS: A SYSTEMATIC BIBLIOMETRIC REVIEW - Yasin, Intan Rafidah; Abdul Razak, Ahmad Zabidi; Abdullah, Zuraidah; Derahman, Rosmanizah; Yasin, Nooni Ezdiani (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Personality traits are pivotal in shaping human behavior and outcomes across diverse contexts, including education, health, work performance, and interpersonal relationships. As interest in this area continues to grow, a substantial body of literature has emerged. However, a structured analysis that captures global publication patterns, research trajectories, and scholarly collaborations remains limited. Thus, this study aims to conduct a comprehensive bibliometric analysis of personality traits research published between 2015 and 2025, to identify publication trends, influential authors, geographical distribution, thematic evolution, and international collaboration patterns. This study addresses the gap in understanding how the field has developed over the past decade by analysing 915 documents retrieved from the Scopus database. Data cleaning and normalisation were performed using OpenRefine, while Scopus Analyzer and VOSviewer software were employed to extract and visualise bibliometric indicators. The analysis revealed a consistent increase in publication output, particularly from 2020 onward. Notably, the United States, United Kingdom, and China were the most productive countries, and network visualisations demonstrated strong co-authorship ties across institutions and continents. Citation analysis identified the most influential authors and sources. At the same time, keyword co-occurrence mapping illustrated a thematic shift from trait measurement to applied domains such as well-being, academic achievement, and organisational behaviour. The findings of this study provide a comprehensive overview of the intellectual landscape and evolution of personality traits research, offering valuable insights for scholars, practitioners, and policymakers. By uncovering key trends and research gaps, this bibliometric review serves as a strategic guide for future investigations and fosters more informed, interdisciplinary, and globally collaborative efforts in the field.